Utilización de excretas de las aves en alimentación de rumiantes - Vargas-González, Emilio (Universidad de Costa Rica, 2013)
Utilization of poultry excreta in rumiant feeding. A study wasconducted to determine chemical composition of poultry escreta in Costa Rica, artd a/so is discurs the use and limitation of these products in ruminant f eeding. Fesu/fs sho wed that the limitant f actor of these by.products is the catcium content; which was 3,1a and 6.13% for broiler titter and tayer litter respectively. Because of this, is not recommend the use of layer manure in ruminant feedinE' The nutrients content studied are in the range of data previoiLsiy reporled, athough is was obserued a great variability in the chemicalcomposition of these materials. The digestible energy valuated for ruminants was 2190 Kcal/kg for the broiler litter and 1748 kcal/kg for the layer litter.'